The 2019 Benguela Niño - Imbol Koungue, Rodrigue Anicet; Brandt, Peter; Lübbecke, Joke; Prigent, Arthur; Martins, Meike Sena; Rodrigues, Regina R. (Frontiers in Marine Science, 2021)
High interannual sea surface temperature anomalies of more than 2ºC were recorded along the coasts of Angola and Namibia between October 2019 and January 2020. This extreme coastal warm event that has been classified as a Benguela Niño, reached its peak amplitude in November 2019 in the Angola Benguela front region. In contrast to classical Benguela Niños, the 2019 Benguela Niño was generated by a combination of local and remote forcing. In September 2019, a local warming was triggered by positive anomalies of near coastal wind-stress curl leading to downwelling anomalies through Ekman dynamics off Southern Angola and by anomalously weak winds reducing the latent heat loss by the ocean south of 15˚S. In addition, downwelling coastal trapped waves were observed along the African coast between mid-October 2019 and early January 2020. Those coastal trapped waves might have partly emanated from the equatorial Atlantic as westerly wind anomalies were observed in the central and eastern equatorial Atlantic between end of September to early December 2019. Additional forcing for the downwelling coastal trapped waves likely resulted from an observed weakening of the prevailing coastal southerly winds along the Angolan coast north of 15˚S between October 2019 and mid-February 2020. During the peak of the event, latent heat flux damped the sea surface temperature anomalies mostly in the Angola Benguela front region. In the eastern equatorial Atlantic, relaxation of cross-equatorial southerly winds might have contributed to the equatorial warming in November 2019 during the peak of the 2019 Benguela Niño. Moreover, for the first time, moored velocities off Angola (11˚S) revealed a coherent poleward flow in the upper 100 m in October and November 2019 suggesting a contribution of meridional heat advection to the near-surface warming during the early stages of the Benguela Niño. During the Benguela Niño, a reduction of net primary production in the Southern Angola and Angola Benguela front regions was observed